Customer Satisfaction in Sri Lankan Retail Banking: Importance of Service Quality - Wijetunga, Dinuka; Goonatillake, Ranjani (My University, 2012)
Abstract: This study attempts to identify the determinants of customer satisfaction in the Retail Banking Sector of Sri Lanka. The findings indicate that service quality is more important in determining satisfaction than service features or price. Out of the different service quality dimensions, Relational Quality and Core Service Quality are found to be more important than the other dimensions (Empathy and Tangibles). The opinions of top-level officers of the Banking sector regarding the important determinants of satisfaction are found to be somewhat different to the findings of the consumer survey.